A chef consultant ala mobile app - Tanoto, Deliony (2016)
A cooking assistant for inexperienced domestic or student to cook a simple dish. Recipes provided by the experienced contributors who wants to share their easy and fast recipe for the app community and interact with one another to exchange information through the app.